Pengaruh Kepercayaan dan Pengalaman Terhadap Loyalitas Nasabah Bank Jago Syariah di Jambi - M. Rikcy; Efni Anita; Nurfitri Martaliah (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to examine the influence of trust and customer experience on customer loyalty at Bank Jago Syariah in Jambi. The rapid growth of Islamic digital banking requires financial institutions not only to attract new customers but also to maintain the loyalty of existing customers. Trust and customer experience are considered important factors that can influence customer loyalty in the use of digital banking services. This study employed a quantitative approach with a causal associative research design. The population consisted of all Bank Jago Syariah customers in Jambi, while the sample included 100 respondents selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and coefficient of determination (R²) using SPSS software. The results indicate that trust has a positive and significant effect on customer loyalty. Customer experience also has a positive and significant effect on customer loyalty. Furthermore, trust and customer experience simultaneously have a positive and significant effect on customer loyalty at Bank Jago Syariah in Jambi. These findings suggest that higher levels of trust and better customer experiences lead to stronger customer loyalty. Therefore, Bank Jago Syariah should continuously enhance service security, maintain customer trust, and improve customer experience to strengthen long-term customer loyalty.